2011
DOI: 10.1158/1078-0432.ccr-11-0060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epstein-Barr Virus–Induced Gene 3 as a Novel Serum and Tissue Biomarker and a Therapeutic Target for Lung Cancer

Abstract: Purpose: This study aims to identify novel biomarkers and therapeutic targets for lung cancer. Experimental Design: We carried out gene expression profile analysis of 120 lung cancers to screen for genes encoding transmembrane/secretory molecules that are commonly transactivated in lung cancers. Epstein-Barr virus-induced gene 3 (EBI3), which encodes a secretory glycoprotein, was selected as a good candidate. Immunohistochemical staining using tissue microarray consisting of 414 non-small cell lung cancers was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 48 publications
(51 reference statements)
3
68
1
1
Order By: Relevance
“…EBI3 was also found to be highly expressed in patients with non-small cell lung cancer (10). Furthermore, strong EBI3 expression in lung cancer tissues has been revealed to be correlated with a poor patient prognosis (10).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…EBI3 was also found to be highly expressed in patients with non-small cell lung cancer (10). Furthermore, strong EBI3 expression in lung cancer tissues has been revealed to be correlated with a poor patient prognosis (10).…”
Section: Discussionmentioning
confidence: 98%
“…Previously, certain studies have revealed the presence of EBI3 overexpression in a series of tumors (8)(9)(10)(11). EBI3 was also found to be highly expressed in patients with non-small cell lung cancer (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations